Subduction metamorphism in the Himalayan ultrahigh-pressure Tso Morari massif: an integrated geodynamic and petrological modelling approach - Palin, R; Reuber, G; White, R; Kaus, B; Weller, O (Elsevier, 2017)
The Tso Morari massif is one of only two regions where ultrahigh-pressure (UHP) metamorphism of subducted crust has been documented in the Himalayan Range. The tectonic evolution of the massif is enigmatic, as reported pressure estimates for peak metamorphism vary from ∼2.4 GPa to ∼4.8 GPa. This uncertainty is problematic for constructing large-scale numerical models of the early stages of India–Asia collision. To address this, we provide new constraints on the tectonothermal evolution of the massif via a combined geodynamic and petrological forward-modelling approach. A prograde-to-peak pressure–temperature–time (P–T–t) path has been derived from thermomechanical simulations tailored for Eocene subduction in the northwestern Himalaya. Phase equilibrium modelling performed along this P–T path has described the petrological evolution of felsic and mafic components of the massif crust, and shows that differences in their fluid contents would have controlled the degree of metamorphic phase transformation in each during subduction. Our model predicts that peak P–T conditions of ∼2.6–2.8 GPa and ∼600–620 ∘C, representative of 90–100 km depth (assuming lithostatic pressure), could have been reached just ∼3 Myr after the onset of subduction of continental crust. This P–T path and subduction duration correlate well with constraints reported for similar UHP eclogite in the Kaghan Valley, Pakistan Himalaya, suggesting that the northwest Himalaya contains dismembered remnants of what may have been a ∼400-km-long UHP terrane comparable in size to the Western Gneiss Region, Norway, and the Dabie–Sulu belt, China. A maximum overpressure of ∼0.5 GPa was calculated in our simulations for a homogeneous crust, although small-scale mechanical heterogeneities may produce overpressures that are larger in magnitude. Nonetheless, the extremely high pressures for peak metamorphism reported by some workers (up to 4.8 GPa) are unreliable owing to conventional thermobarometry having been performed on minerals that were likely not in equilibrium. Furthermore, diagnostic high-P mineral assemblages predicted to form in Tso Morari orthogneiss at peak metamorphism are absent from natural samples, which may reflect the widespread metastable preservation of lower-pressure assemblages in the felsic component of the crust during subduction. If common in such subducted continental terranes, this metastability calls into question the reliability of geodynamic simulations of orogenesis that are predicated on equilibrium metamorphism operating continuously throughout tectonic cycles.